Rheological characteristics of synthetic wax-modified asphalt binders - Iwański, M.; Mazurek, G. (Polimery, 2012)
This paper presents the test results of modification of bitumen 35/50 with synthetic aliphatic wax (SW) obtained during the Fisher-Tropsha synthesis. The aim of the modification is an improvement of rheological properties of the bitumen as well as possibilities to lay the asphalt pavement at decreased compaction temperature by up to 30 °C. Experiments have confirmed that the modification of asphalt with synthetic wax resulted in beneficial changes in complex modulus (G*) and phase angle (d) of modified bitumen 35/50. In consequence, the modified bitumen increased resistance of the asphalt pavement to permanent deformation and decreased the compaction temperature to 100 °C. On the basis of the MSCR test it was revealed that the existence of aliphatic wax in bitumen compound affected the compliance (Jnr) and elastic recover (R) of bitumen. It resulted in an increase in the resilient modulus of elasticity of asphalt pavement and also it will contribute to its higher durability.